2010
DOI: 10.2174/1875934301003010155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycling Different Leachate Volumes on Refuse Anaerobic Degradation

Abstract: Abstract:The aim of this work was to determine the appropriate moisture regime, attained by leachate recycling, to achieve the highest municipal solid waste (MSW) biodegradation rate. To this end, leachate characteristics, methane production rate and changes in degraded refuse were studied. Twenty laboratory-scale bioreactors were loaded with MSW from the landfill of Pátzcuaro (Mexico), four were used as controls and sixteen were operated under leachate recycling to achieve moisture content regimes (%MC) of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Studies have shown that leachate recirculation produces stabilized leachates with good BOD/COD ratio [16]. Although a land ll may have most advanced leachate management practices, recycling process, in some researches, resulted in an imbalance between acidogenesis and methanogenesis in the land ll leachate [17,18]. The good BOD/COD ratio may mask a de ciency in the natural process.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that leachate recirculation produces stabilized leachates with good BOD/COD ratio [16]. Although a land ll may have most advanced leachate management practices, recycling process, in some researches, resulted in an imbalance between acidogenesis and methanogenesis in the land ll leachate [17,18]. The good BOD/COD ratio may mask a de ciency in the natural process.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that leachate recirculation produces stabilized leachates with good BOD/COD ratio [16]. Although a land ll may have most advanced leachate management practices, recycling process, in some researches, resulted in an imbalance between acidogenesis and methanogenesis in the land ll leachate [17,18]. The good BOD/COD ratio may mask a de ciency in the natural process.…”
Section: Resultsmentioning
confidence: 99%
“…Un factor fundamental en estas reacciones es el agua. Numerosos autores han observado cómo la velocidad de degradación crece drásticamente al aumentar el contenido de humedad del residuo (Benbelkacem et al 2010, Chugh et al 1998, Hernández-Berriel et al 2010, Olay-Romero et al 2014. Por eso la técnica clásica de clausura de vertederos aislando el residuo con capas impermeables en superficie consigue no sólo reducir la cantidad de lixiviados sino también parar la generación de gas, al detener la biodegradación dejando seco el vertedero.…”
Section: La Importancia De La Humedadunclassified